Developing effective policy strategies to retain health workers in rural Bangladesh: a policy analysis - Rawal, Lal B; Joarder, Taufique; Islam, Sheikh Md. Shariful; Uddin, Aftab; Ahmed, Syed Masud (© 2015 Rawal et al.; licensee BioMed Central., 2016)
This article was published in Human Resources for Health [ © 2015 Rawal et al.; licensee BioMed Central] and the definite version is available at: https://human-resources-health.biomedcentral.com/articles/10.1186/s12960-015-0030-6